Fibroepithelial neoplasms of the breast. Issue 4 (April 2017) - Hanby, Andrew M.; Millican-Slater, Rebecca; Dessauvagie, Benjamin
Abstract: Fibroepithelial neoplasms include a large number of common lesions encountered in both symptomatic and breast screening practice. Nearly all are fibroadenomas and are harmless, but they can present a range of differing histologies. The area of most concern is the separation of fibroadenomas from phyllodes tumours, arguably an arbitrary exercise at the benign end of the spectrum. What is most important to achieve is the recognition of those lesions in the fibroadenoma-phyllodes spectrum with the potential to do harm, either in the form of recurrence or metastases. These are few in number and the key features to identify, with the rare exception of carcinoma arising in these lesions, are those that signify a progression to stromal autonomy. Such features include stromal overgrowth, stromal invasion, stromal cell atypia and stromal mitotic activity. These need to be analysed together, not in isolation. Necrosis and heterotypic elements in particular are suggestive of frank malignancy.